(untitled) (Marketing Journal, 2025)
This article analyzes the factors influencing the development of marketing strategies and the enhancement of competitiveness among farming enterprises in the agricultural sector. The research focuses on essential elements such as strategic marketing planning, the use of digital technologies and innovative tools, market segmentation, pricing policy, and branding. Additionally, the study highlights practical approaches including the production of environmentally friendly products, quality improvement, and the use of online sales platforms. The results demonstrate that well- structured marketing strategies enable farmers to access wider markets and increase economic efficiency.